1998
DOI: 10.1038/bjc.1998.195
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the presentation and growth of thyroid cancer

Abstract: Summary Seasonal variation has been described in the presentation and growth of several malignant tumours, including cancers of the breast, uterus, uterine cervix, urinary bladder, liver, lymphatic system and skin, although the mechanisms are not known. We herein describe a circannual rhythm for thyroid cancer (total = 2627), with significantly more cases presenting during the late autumn and winter. In a subset of these cases (127 papillary carcinomas), significant seasonal variations with highest values in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Finally, it has been shown a circannual variation in tumor cell proliferation in non-Hodgkin's lymphomas (Smaaland R et al, 1993) and in thyroid tumors (Akslen LA & Sothern RB, 1998), with acrophases in winter for both studies. Consequently, we may further hypothesize that chemotherapy is more active in wintertime as tumor cells are more proliferating.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, it has been shown a circannual variation in tumor cell proliferation in non-Hodgkin's lymphomas (Smaaland R et al, 1993) and in thyroid tumors (Akslen LA & Sothern RB, 1998), with acrophases in winter for both studies. Consequently, we may further hypothesize that chemotherapy is more active in wintertime as tumor cells are more proliferating.…”
Section: Discussionmentioning
confidence: 91%
“…[11][12][13][14][15][16] Such seasonality has been found not only in animals 16,19,33,34 but also in normal humans 18,20,35,36 and associated with some diseases. [5][6][7][8]17,37,38 These previous studies have suggested that seasonal variation of the immune function might also affect the clinical course of chronic liver diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Any factors that may affect any of these can affect the clinical course of chronic hepatitis B. 3 Seasonal variation has been documented in the exacerbation and attributable mortality of a number of illnesses, [4][5][6] including some liver diseases. 7,8 Whether similar trends exist in chronic hepatitis B is not definitively known.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer incidence, in general, and breast cancer incidence, in particular, are not randomly distributed throughout the year [1][2][3][4][5][6][7][8][9][10][11]. Abundant epidemiologic literature suggests that human breast cancer is diagnosed more often during spring, both in the Northern and Southern Hemispheres [1,3,4,8,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%